Vocational education - new generation teaching material for people with ASD - Kossewska, Joanna (Social Welfare: Interdisciplinary Approach, 2015)
New generation multimedia teaching material for people with autism vocational education was built under the international cooperation with the theoretical assumptions of personalistic and the person-oriented approach. The didactic material combined of two main parts: general vocational skills training and particular skills adequate in four work places training (library, hotel, kitchen, office), was evaluated during the microgenetic training sessions with ASD adults clients. The results of metha-analysis are presented.